2017
DOI: 10.1073/pnas.1616608114
|View full text |Cite
|
Sign up to set email alerts
|

New perspective on spring vegetation phenology and global climate change based on Tibetan Plateau tree-ring data

Abstract: Phenological responses of vegetation to climate, in particular to the ongoing warming trend, have received much attention. However, divergent results from the analyses of remote sensing data have been obtained for the Tibetan Plateau (TP), the world's largest highelevation region. This study provides a perspective on vegetation phenology shifts during 1960-2014, gained using an innovative approach based on a well-validated, process-based, tree-ring growth model that is independent of temporal changes in techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
92
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 208 publications
(115 citation statements)
references
References 51 publications
10
92
2
Order By: Relevance
“…Firstly, the significant correlations between the modeled results and actual tree-ring width chronologies (TRW) suggest that the model performance is robust (95% series reaches the significance level of p < 0.01, and the remaining 5% series is significant at the level of p < 0.03). Secondly, the derived phenological series are generally consistent with the available monitored results in the study region [18]. Thirdly, the regionally averaged phenological variability closely matches with the vegetation green-up series derived from remote sensing data over their common period 1982-2011, as conducted by Yang et al [18].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Firstly, the significant correlations between the modeled results and actual tree-ring width chronologies (TRW) suggest that the model performance is robust (95% series reaches the significance level of p < 0.01, and the remaining 5% series is significant at the level of p < 0.03). Secondly, the derived phenological series are generally consistent with the available monitored results in the study region [18]. Thirdly, the regionally averaged phenological variability closely matches with the vegetation green-up series derived from remote sensing data over their common period 1982-2011, as conducted by Yang et al [18].…”
Section: Discussionsupporting
confidence: 83%
“…Secondly, the derived phenological series are generally consistent with the available monitored results in the study region [18]. Thirdly, the regionally averaged phenological variability closely matches with the vegetation green-up series derived from remote sensing data over their common period 1982-2011, as conducted by Yang et al [18]. Hence, in comparison to the monitoring results that could only detect connections from a limited number of trees and years [10][11][12], our analysis is thus able to deepen the understanding of the relationships between the stem radial growth of a tree and the start (SOS), the end (EOS), and the length (LOS) of cambial activity.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…One limitation of this study is that partitioning larval otolith growth due to temperature increase vs. growing season length was not based on the entire growing season of YOY (as larvae could not be collected from all sites at the end of the growing season). In addition, a very recent terrestrial study on the TP has also proposed comparable methods of using tree-ring microstructure chronology data to examine changes in spring vegetation phenology (Yang et al, 2017). Another potential limitation in this study is that we assumed that temperature was the key factor influencing otolith growth and we did not consider other factors such as food, which may be important in some circumstances (Hinrichsen, Voss, Huwer, & Clemmesen, 2010;Schismenou et al, 2014).…”
Section: Dendrochronological Methods To Study Phenological Changes mentioning
confidence: 98%
“…In terms of seasonal mean GPP, we found that spring warming significantly promoted the GPP of alpine grassland. In fact, some studies reported that the start of the vegetation growing season in the Tibetan Plateau exhibited an advancing trend during the past few decades, which maybe the reason causing the increase of spring GPP (G. Zhang et al, ; Yang et al, ). Although increasing temperature in autumn may extend the growth season, there was no significant influence on GPP changes.…”
Section: Resultsmentioning
confidence: 99%